SWOT Matrix Strategy Formulation using SMART GE 1.0 on Jordan Plastics - Guruh Taufan Hariyadi (AMIK Jakarta Teknologi Cipta Semarang, 2020)
The plastic packaging industry is an industry that has high growth and its potential is still large in line with the increasing demand for national plastic products, which has increased by 5% in the last 5 years. Jordan Plastics also plays a role in the absorption of labor in the plastics industry. In facing the competition in the plastic industry, PT Jordan Plastic formulated its strategy through a SWOT analysis using data from the evaluation of internal factors and evaluation of external factors, then forming a quadrant of company position using Smart GE 1.0. PT Jordan Plastic is in an aggressive quadrant, so the strategies that need to be used are market penetration, market development, product development, diversification related to core products, and diversification not related to core products.